Robotic process automation : UiPath RPA developer masterclass. (Packt Publishing, 2022)
Explore and master Robotics Process Automation and gain the skills you need to automate real-world business and IT processes using UiPath. About This Video Explore the field of Robotic Process Automation and get a deep understanding of its fundamentalss Discover a comprehensive beginners' course for developers in the RPA field with easy-to-follow instructions Apply automation techniques on Excel, PDF, Mail, desktop, web, invoicing, and scraping data from websites In Detail Robotic Process Automation (RPA) is a game-changing technology that is designed to automate high-volume, recurring processes that consume a significant amount of a worker's time. Take advantage of this opportunity to get trained in one of the most in-demand skills and prepare for future employment. This course combines the best of two worlds by giving you a proper tech primer followed by many practice exercises. You will get your hands dirty and learn by doing, but you will also have us by your side supporting you in your learning process. We (authors) have simply built the course we wished we had when starting out on our own RPA developer careers. This course starts with introducing you to RPA and how it works. You will install the UiPath Studio developer software interface and go through its workings, then look at programming concepts important for RPA development. You will design, develop, and deploy advanced robots from scratch. You will see best practices for automating business processes and finally explore what to do next to further improve your skills. By the end of this course, you will have learned best practices and important programming concepts for RPA development. You will have also designed, developed, and deployed robots by automating seven processes, and learned how to grow as an RPA developer. Audience This course is for individuals who want to kickstart their Robotic Process Automation development journey and want to land a job as an RPA developer. Students who want to learn best practices for automating business processes from RPA professionals, and developers who want to learn the fundamental programming concepts important for RPA development will also benefit from this course. As a prerequisite, you need a modern Windows computer with an internet connection (UiPath does not have a Mac version) and a desire to learn about one of the most promising emerging technologies right now.